Synthesis of diverse dihydropyrimidine-related scaffolds by fluorous benzaldehyde-based Biginelli reaction and post-condensation modifications - Piqani, Bruno; Zhang, Wei (Beilstein Journal of Organic Chemistry, 2011)
Dihydropyrimidinones and dihydropyrimidinethiones generated from the Biginelli reactions of perfluorooctanesulfonyl-attached benzaldehydes are used as common intermediates for post-condensation modifications such as cycloaddition, Liebeskind–Srogl reaction and Suzuki coupling to form biaryl-substituted dihydropyrimidinone, dihydropyrimidine, and thiazolopyrimidine compounds. The high efficiency of the diversity-oriented synthesis is achieved by conducting a multicomponent reaction for improved atom economy, under microwave heating for fast reaction, and with fluorous solid-phase extractions (F-SPE) for ease of purification.
Keywords: Biginelli reaction; dihydropyrimidine; diversity-oriented synthesis; fluorous; Suzuki coupling

(untitled) - Kappe, C. O. (Acc. Chem. Res., 2000)

(untitled) - Kappe, C. O. (Eur. J. Med. Chem., 2000)

(untitled) - Biginelli, P. (Gazz. Chim. Ital., 1893)

(untitled) - Kappe, C. O.; Stadler, A. (Org. React., 2004)

Multicomponent Reactions - Kappe, C. O. (The Biginelli Reaction, 2005)

(untitled) - Studer, A.; Jeger, P.; Wipf, P.; Curran, D. P. (J. Org. Chem., 1997)

(untitled) - Zhang, W.; Curran, D. P. (Tetrahedron, 2006)

(untitled) - Larhed, M.; Hallberg, A. (J. Org. Chem., 1996)

(untitled) - Larhed, M.; Hoshino, M.; Hadida, S.; Curran, D. P.; Hallberg, A. (J. Org. Chem., 1997)

(untitled) - Kadam, A.; Zhang, Z.; Zhang, W. (Curr. Org. Synth., 2011)

(untitled) - Zhang, W. (Chem. Rev., 2009)

(untitled) - Zhang, W. (Comb. Chem. High Throughput Screening, 2007)

(untitled) - Zhang, W.; Chen, C. H.-T.; Lu, Y.; Nagashima, T. (Org. Lett., 2004)

(untitled) - Kappe, C. O.; Dallinger, D. (Nat. Rev. Drug Discovery, 2006)

(untitled) - Dallinger, D.; Kappe, C. O. (Nat. Protoc., 2007)

(untitled) - Wang, X.-C.; Quan, Z.-J.; Zhang, Z.; Liu, Y.-J.; Ji, P.-Y. (Lett. Org. Chem., 2007)

(untitled) - Quan, Z.-J.; Zhang, Z.; Wang, J.-K.; Wang, X.-C.; Liu, Y.-J.; Ji, P.-Y. (Heteroat. Chem., 2008)

(untitled) - Liebeskind, L. S.; Srogl, J. (J. Am. Chem. Soc., 2000)

(untitled) - Villalobos, J. M.; Srogl, J.; Liebeskind, L. S. (J. Am. Chem. Soc., 2007)

(untitled) - Prokopcová, H.; Kappe, C. O. (J. Org. Chem., 2007)

(untitled) - Prokopcová, H.; Kappe, C. O. (Angew. Chem., Int. Ed., 2009)